∆υναµέναι καὶ ὀνοµαστοτάται πόλεις. Choice and description of the cities in Strabo's Book III - Castro-Páez, Encarnación (Editorial Universidad de Alcalá - Editorial Universidad de Sevilla, 2022)
This paper aims to be a summary presentation of the criteria and perspectives involved in the choice and description of the cities mentioned by Strabo in Book III of his Geography. To this end, by way of introduction and before delving into the pages devoted to Iberia in a monographic way, some questions will be dwelt on which, although widely known, should not be overlooked when trying to understand the chorographical description constructed by Strabo. Having contextualised Strabonian literary production as a whole, we will focus our attention on book III and, more specifically and as has already been mentioned, on the elements that mark the way cities are presented in Hispanic territories.
Keywords: Geografía antigua; Estrabón; Pólis